2021
DOI: 10.1212/wnl.0000000000011314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ibudilast on MRI Measures in the Phase 2 SPRINT-MS Study

Abstract: OBJECTIVE:For progressive forms of multiple sclerosis, determine whether ibudilast has an effect on brain volume and new lesions.METHODS:A randomized, placebo controlled, blinded study evaluated ibudilast at a dose of up to 100 mg over 96 weeks in primary and secondary progressive multiple sclerosis. In this secondary analysis of a previously reported trial, secondary and tertiary endpoints included gray matter atrophy, new or enlarging T2 lesions as measured every 24 weeks, and new T1 hypointensities at 96 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Despite having positive effects on MRI measures of progressive tissue injury, ibudilast did not have a beneficial effect on the development of new or enlarging T2 lesions. 22 This dissociation between measures of neurodegeneration and neuroinflammation, along with our observations that NfL was unchanged by ibudilast, suggests that NfL may be more sensitive to track neuroaxonal injury that is associated with acute focal inflammatory disease activity in MS (i.e. new gadolinium-enhancing lesions and T2 lesions) than other chronic pathologies present in progressive MS (i.e.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Despite having positive effects on MRI measures of progressive tissue injury, ibudilast did not have a beneficial effect on the development of new or enlarging T2 lesions. 22 This dissociation between measures of neurodegeneration and neuroinflammation, along with our observations that NfL was unchanged by ibudilast, suggests that NfL may be more sensitive to track neuroaxonal injury that is associated with acute focal inflammatory disease activity in MS (i.e. new gadolinium-enhancing lesions and T2 lesions) than other chronic pathologies present in progressive MS (i.e.…”
Section: Discussionmentioning
confidence: 63%
“…10 One previous study of fingolimod and preliminary reports of several approved MS therapies, including alemtuzumab, natalizumab, pegylated interferon, and ocrelizumab, found that these therapies are associated with lower serum NfL levels. 18–20 Although ibudilast has several anti-inflammatory effects in vitro (described above), it does not reduce the development of new inflammatory brain lesions in either relapsing MS 21 or our trial of progressive MS 22 , and thus does not appear to have clinically relevant anti-inflammatory activity in MS. Rather than acting as an anti-inflammatory in the brain of patients with progressive MS, ibudilast may protect neurons in lesions from continued damage and decline after previous inflammatory injury. 13…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing trial in treatment-seekers may serve to address this outstanding question as well, as treatment-seeking populations tend to report a greater number of AUD symptoms and consume more drinks per drinking day (Ray et al, 2017b). Severity of AUD and overall brain pathology may be particularly relevant given that ibudilast has been studied for a host of brain-based biomarkers in clinical trials for multiple sclerosis (Fox et al, 2018;Naismith et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the initial trial results showed an overall reduction in the rate of cortical thickness loss, 1 and we again found a similar pattern according to phenotype: this effect was principally driven by the PPMS subjects. Results of conventional imaging outcomes are reported in a separate publication 2 …”
Section: Discussionmentioning
confidence: 99%
“…We previously reported 1 a significant reduction in the rate of cerebral atrophy progression as determined by brain parenchymal fraction (BPF) assessments in people with progressive multiple sclerosis (MS) in a randomized phase 2 clinical trial, “SPRINT‐MS,” comparing ibudilast to placebo. Detailed results of the MRI outcomes from the SPRINT‐MS trial were recently reported 2 . Despite recognition as different clinical disease phenotypes, 3 primary progressive (PPMS) and secondary progressive (SPMS) are often viewed as being more similar than different pathologically 4 .…”
Section: Introductionmentioning
confidence: 99%